Structural and functional impacts of ER coactivator sequential recruitment - Yi, Ping (Mol Cell, 2017)
Nuclear receptors recruit multiple coactivators sequentially to activate transcription. This “ordered” recruitment allows different coactivator activities to engage the nuclear receptor complex at different steps of transcription. Estrogen receptor (ER) recruits SRC-3 primary coactivator and secondary coactivators p300/CBP and CARM1. CARM1 recruitment lags behind the binding of SRC-3 and p300 to ER. Combining cryo-EM structure analysis and biochemical approaches, we demonstrate that there is a close crosstalk between early and late recruited coactivators. The sequential recruitment of CARM1 not only adds a protein arginine methyltransferase activity to the ER-coactivator complex but also alters the structural organization of the pre-existing ERE/ERα/SRC-3/p300 complex. It induces a p300 conformational change and significantly increases p300 HAT activity on histone H3K18 residues, which in turn promotes CARM1 methylation activity on H3R17 residues to enhance transcriptional activity. This study reveals a structural role for a coactivator sequential recruitment and biochemical process in ER-mediated transcription.